The patients view on genetics and functional imaging for precision medicine: a willingness-to-pay analysis - Clasen, Kerstin; Gani, Cihan; Schroeder, Christopher; Riess, Olaf; Zips, Daniel; Schöffski, Oliver; Clasen, Stephan (Personalized medicine, 2022)
Lay abstract A study of the patients preferences in diagnostic approaches where patients were asked if they would hypothetically pay out-of-pocket money for particular procedures. However, in regard to personalized medicine (specifically selected for a single person) genetic testing especially might imply ethical concerns. A questionnaire was designed to compare preferences for imaging and genetic testing in cancer patients and to evaluate potential ethical concerns. Comparing the options of imaging and genetics showed comparable values of out-of-pocket money the patients were willing to pay. Ethical concerns about genetic testing were minor. Treatment success was the top priority irrespective of the diagnostic modality. Most patients valued personalized approaches and rated the benefits of overriding importance irrespective of modality or ethical concerns.
CRIS-Team WoS Importer:2022-01-14